DI-087 Spontaneous reporting of adverse drug reactions in a second level hospital: is pharmacovigilance well targeted?. (24th March 2015) - Borràs Trias, L; Pontes García, C; García Argelaguet, M; De Castro Julve, M; Raich Montiu, L; Gorgas Torner, MQ
Abstract : Background: It has been repeatedly reported that up to 7% of patients have serious adverse drug reactions (ADR) during hospital admissions. Hospital-based pharmacovigilance aims to detect previously unknown serious ADRs arising during differential diagnosis, with focus on special populations, but relies on spontaneous reporting by physicians. As a part of process auditing, we reviewed spontaneous ADR reports received by the Hospital Pharmacy since the introduction of an intranet-based form for reporting, Purpose: To assess whether the system is targeted to detect previously unknown ADRs and serious ADRs in special populations. Material and methods: All reports received between January 2011 and December 2013 were reviewed. The suspected drugs and whether they had a regulatory requirement for additional monitoring (i.e. a black triangle on the label), the seriousness of the reaction and the novelty of the clinical association (i.e. absent from the summary of product characteristics) were described. Results: There were 53, 332 admissions during the period, thus 3, 733 serious ADRs were expected (7%). Only 114 notifications were received, which represents 3% of all potential reports, related to 108 patients (13% paediatric and 24% aged ≥75 years), and involving 143 suspected drugs of which 18% had regulatory requirements for additional monitoring. 72% of reports met the seriousness criteria. Only 5% of the reports described previously unknown associations, of which half were confirmed as at least possible reactions: two cases of hepatitis associated with metamizole and rizatriptan respectively, and leukocytoclastic vasculitis associated with tocilizumab. Conclusion: Our audit pointed out serious under-reporting but highly focused reports: most were serious events, one third involved special populations, and one fifth drugs with a regulatory requirement for additional monitoring. Actions to improve notifications are required, but the fact that 3% of the reports were relevant suggests that the system is already focused. References and/or acknowledgements: Multidisciplinary team. No conflict of interest.